Regulasi Emosi Melaluwi Al-‘Afwu: Studi Komparatif Tafsir Ibnu Katsir dan Tafsir Al-Misbah atas QS. Yusuf: 92 - Anita Luthfiana Harahap; Maharani; Mardian Idris Harahap; Rahayu Fuji Astuti (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This article examines the significance of al-'afwu (forgiveness) in QS. Yusuf: 92 through the lens of emotional regulation. The study focuses on how the phrase "lā tasrība 'alaikumul-yaum" represents the peak of Prophet Yusuf's emotional management regarding his past. This study compares the interpretation of Ibn Kathir, which is bil ma'tsur in style, with the interpretation of M. Quraish Shihab, which follows an adabi ijtima'i (socio-literary) style, using a muqaran (comparative) method and a maudhu'i (thematic) tafsir approach. The research findings indicate that Ibn Kathir emphasizes forgiveness within a theocentric dimension, where emotional regulation is based on surrendering judgment to Allah (tafwidh). On the other hand, M. Quraish Shihab performs a more comprehensive psychological contextualization, viewing al-'afwu as an effort to develop an individual's inner self from the shackles of resentment to achieve shadr al-halim (an open heart). These differences show that while classical tafsir focuses on eschatology (reward and God's forgiveness), contemporary tafsir focuses more on mental health and social reactions. This research demonstrates that the terminology of al-'afwu in the Qur'an is not merely the waiving of legal claims, but rather a Qur'anic tool to stabilize the human condition in facing destiny.